Strategi Promosi Pada Griya Kain Tuan Kentang - Amanda Febrianti; Hanifati Burhan; Yulia Pebrianti (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2021)
This study aims to determine the strategies used by Griya Kain Tuan Kentang to see objectively the internal and external conditions of the company in an effort to compete with other shopping tours. The formulation of the problem of this research is how the promotion strategy carried out by Griya Kain Tuan Kentang. This research is a qualitative research with descriptive analysis. This research was conducted by collecting respondents using a questionnaire with a non probability sampling technique with accidental sampling. This study uses a SWOT analysis. The results of the study indicate that using strengths are taking advantage of existing opportunities. The highest strength is Griya Kain Tuan Kentang as visitors who know information about Griya Kain Tuan Kentang by word of mouth and the highest opportunity is that technological progress has a good impact on product promotion at Griya Kain Tuan Kentang. It would be better if Griya Kain Tuan Kentang can continuously promote both print and electronic media, one of which is through Instagram and Facebook.